2012
DOI: 10.1128/jvi.00196-12
|View full text |Cite
|
Sign up to set email alerts
|

Shelterin Dysfunction and p16 INK4a -Mediated Growth Inhibition in HIV-1-Specific CD8 T Cells

Abstract: c HIV-1-specific cytotoxic T cell responses are expanded during advanced HIV-1 infection but seem unable to effectively protect the host against disease progression. These cells are able to produce gamma interferon and remain metabolically active but have defective proliferative activities, shortened telomeric DNA, and other signs of accelerated aging. To investigate the molecular mechanisms underlying the premature senescence of HIV-1-specific T cells, we focused here on the expression and function of a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This compensatory mechanism is defective in RA T cells [14,53]. Insufficient telomeric repair has also been reported for HIV T cells due to abnormalities in the telomeric protection complex of the shelterin proteins, thereby leaving chromosomal ends exposed [70] * .…”
Section: Dna Damage-induced Immunosenescence In Rheumatoid Arthritismentioning
confidence: 99%
“…This compensatory mechanism is defective in RA T cells [14,53]. Insufficient telomeric repair has also been reported for HIV T cells due to abnormalities in the telomeric protection complex of the shelterin proteins, thereby leaving chromosomal ends exposed [70] * .…”
Section: Dna Damage-induced Immunosenescence In Rheumatoid Arthritismentioning
confidence: 99%
“…The telomere length in HIV-specific CD8 T cells approaches the Hayflick limit for terminal senescence during progressive HIV infection [22, 55, 68]. The shortened telomeres observed in HIV-specific CD8 T cells correlated with reduced expression of proteins of the shelterin complex and disruption of shelterin complex formation [69]. The shelterin complex is a group of nucleoproteins found at the terminal ends of chromosomal DNA whose function is to protect telomeric DNA and regulate telomerase activity [70, 71].…”
Section: Increasing Cd8 T Cell Dysfunction Is Associated With the mentioning
confidence: 99%
“…This lead to improved clinical outcomes in SIV infected rhesus macaques treated with PD-1 blocking antibody [74]. These data suggest that HIV-specific CD8 T cells with shortened telomeres are not in a state of irreversible DNA repair and that recovery of telomere length may contribute to the rescue of cytotoxic effector functions [69]. However, Lichterfeld et al also found that despite an observed increase in telomere length, PD-1 blocking antibody treatment did not result in stabilization to normal levels in the protein expression of the components of the shelterin complex that protect exposed telomere ends and which could influence long term survival [69].…”
Section: Increasing Cd8 T Cell Dysfunction Is Associated With the mentioning
confidence: 99%
“…TPP1, a nucleoprotein pivotal for maintaining telomere integrity and homeostasis, showed elevated levels in our aged, infected samples. However, TPP1’s function in chronically HIV-infected patients remains unclear [ 54 , 55 ]. We noted an upregulation of the genomic instability marker, zinc metalloproteinase ZMPSTE24, which has been associated with increased levels of inflammation and an increase in progerin mRNA, both recognized as indicators of aging [ 56 ].…”
Section: Discussionmentioning
confidence: 99%